Analysis of COVID-19 vaccine adverse drug reactions reported among sultan Qaboos university hospital staff - al-Busaidi, Bushra H.; al-Riyami, Intisar M.; Ba Wazir, Hashim; al-Zakwani, Ibrahim S. (Sultan Qaboos University medical journal, 2024)
Objectives: This study aimed to report any suspected adverse drug reactions (ADRs) experienced by all vaccinated staff and students in a tertiary teaching hospital following COVID-19 vaccination. Methods: This retrospective study was conducted during the COVID-19 vaccination campaign at Sultan Qaboos University and Hospital in Muscat, Oman, from August to September 2021. An online survey was generated and sent to all staff and students via email and text messages. An announcement was made on the hospital website with a link to the survey. Results: A total of 8,421 individuals reported being vaccinated at least once with a total of 11,468 doses administered from January to July 2021; 8,014 staff and students received the Pfizer-Biotech vaccine while 3,454 staff and students received the Oxford-AstraZeneca vaccine. The survey received a total of 3,275 responses (response rate = 38.8%). Of these, 741 individuals (22.6%) experienced an ADR after vaccination and 67.2% (n = 498) were females (P <0.001). The majority of the ADRs reported were fever and chills (19.7%) followed by localised pain and swelling at the injection site (18.8%). Other ADRs such as hair loss (0.5%) were reported, and one staff/student reported a clot in the right leg. Among the responders, 27.0% considered their ADRs as mild while 25.0% considered them as severe. Conclusions: In the study cohort, mild symptoms of COVID-19 vaccines were reported. Females experienced more ADRs compared to males. Long-term observation of ADRs to the vaccines and follow-up monitoring should be done on subjects to preclude any unwanted effects.